Amelia Valcárcel, Feminismo en el mundo global, Cátedra/Universitat de València/Instituto de la Mujer, Colección Feminismos, Madrid, 2008 - Domínguez, Héctor; Peces, Eva (Foro Interno, 2010)
Sin resumen